2020
DOI: 10.20535/2410-8286.200720
|View full text |Cite
|
Sign up to set email alerts
|

Translation Assesssment: Is There Anything to Be Tested Objectively?

Abstract: Due to the complex and integrative nature of translation competence construct, its free of subjectivity assessment is considered quite a challenging task for modern translation pedagogy. The conducted literature review revealed diverse directions and opportunities to raise translation competence assessment objectivity. In this key, there is a need for the further studies focused on the designing and implementing of objective translation tests. Thus, the given paper aims at the development and verification of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…At the same time, the teachers tended to disagree with the idea, evidently due to the difficulty in defining the contribution of each party-the student and ChatGPT-and the lack of understanding in assessing such assignments. In this context, there may be a need to develop and integrate various testing techniques that can be used in the new conditions and realities created by AI in education [26].…”
Section: Academic Integrity Concernsmentioning
confidence: 99%
“…At the same time, the teachers tended to disagree with the idea, evidently due to the difficulty in defining the contribution of each party-the student and ChatGPT-and the lack of understanding in assessing such assignments. In this context, there may be a need to develop and integrate various testing techniques that can be used in the new conditions and realities created by AI in education [26].…”
Section: Academic Integrity Concernsmentioning
confidence: 99%
“…also notices that different translation scholars interpret the term translation assessment inconsistently, depending on their theoretical positions. Therefore, there are a number of studies about translation assessment, for instance, mixed researches (Nikolaeva and Korol, 2021;Korol, 2020;Korol, 2021), quantitative researches (Akulina and Tikhonova, 2021;Su, 2022;Angelone, 2020) and qualitative researches (Han, 2020;Huang and Xin, 2020). However, there is a lack of systematic reviews on translation assessment despite many studies, let alone any using bibliometric analysis and visualization, such as research hotspots and trends.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed review of the current research state of translation assessment in modern education can be found in many sources (Han, 2021;Hurtado Albir, 2019;Korol, 2019), while the main peculiarities and requirements for the efficient assessment practices in translation training caused by contemporary advances in didactics, foreign language and translation teaching methodologies are summarised in Korol (2018). The latter include the concurrent performance of evaluative and formative functions by the assessment (Klimkowski, 2019;Robinson, Olvera Lobo, & Gutiérrez-Artacho, 2013;Wang, 2022), the employment of versatile assessment methods and tools for the measurement of particular assessment objects at its different stages, the evaluation of translation process, product and services as the valuable indicators of the students' actual translation competence level, the arrangement of peerand self-assessment as intrinsic components of the efficient translation activity in a modern professional environment (Ge & Pi, 2021;Korol, 2020).…”
Section: Introductionmentioning
confidence: 99%